2015
DOI: 10.3758/s13428-015-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

The relative accuracy and interpretability of five sequential analysis methods: A simulation study

Abstract: A variety of sequential analysis methods exist to quantify close temporal associations between events from direct observation data. In the present study, we compared the relative accuracy and interpretability of five sequentialanalysis methods using simulated data. The methods included three existing approaches (event lag, concurrent interval, and time window) and two proposed modifications of the event lag approach (event lag with contiguous pauses and event lag with noncontiguous pauses) designed to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…We applied the event lag with pauses method to measure behaviour-behaviour contingencies only; we did not measure behaviour-environment contingencies. We used the event lag with pauses method because it has been shown to (1) produce accurate estimates of sequential association regardless of the total number of coded events and (2) adequately control for chance estimates of the sequence of interest (Lloyd et al 2016). To apply this method, all coded events that did not define the sequence of interest were stripped out of the raw data file for each analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied the event lag with pauses method to measure behaviour-behaviour contingencies only; we did not measure behaviour-environment contingencies. We used the event lag with pauses method because it has been shown to (1) produce accurate estimates of sequential association regardless of the total number of coded events and (2) adequately control for chance estimates of the sequence of interest (Lloyd et al 2016). To apply this method, all coded events that did not define the sequence of interest were stripped out of the raw data file for each analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential analysis method, known as event lag with pauses, has been shown to produce accurate estimates of contingency regardless of the total number of coded events and to adequately control for chance estimates of the sequence of interest (Lloyd et al . ). We analysed a set of community‐based observations for each of seven individuals with ID and chronic SIB to address the following research questions: (1) What is the direction and strength of SIB–SIB contingencies in community settings?…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The event lag with contiguous pauses method was selected because decisions regarding which non-key events (i.e., those other than the events in the key sequence) should be analyzed are usually underjustified but can greatly influence the strength and the direction of the sequential association (Lloyd et al, 2015; Yoder & Symons, 2010). An extant simulation study has demonstrated that the event lag with contiguous pauses method resolves the problem of having to justify which non-key events should be included in the computation of a sequential association (Lloyd et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The event lag with contiguous pauses method has also been shown to be more accurate and less correlated with the frequency of chance occurrence of the sequence of interest than three other sequential analysis methods (i.e., time window, concurrent interval, and event lag without pauses; Lloyd et al, 2015). Further detail about the event lag with contiguous pauses method is found in Lloyd et al (2015).…”
Section: Methodsmentioning
confidence: 99%